Preschool teachers’ self-efficacy and children’s motivation on science - Bekirler, Aslı; Dikici Siğirtmaç, Ayperi (Universitas Majalengka, 2024)
This study focuses on two critical factors in science education: Teachers' self-efficacy beliefs and children's motivation. The purpose is to examine the relationship between preschool teachers' self-efficacy beliefs towards science education and children's science motivation, while also exploring potential variations based on specific variables. The sample for this quantitative research included 298 children aged between 60 and 72 months (149 girls, 149 boys) and their 149 teachers. The participant children are randomly selected from each teacher's class, with an equal representation of girls and boys. Data were collected using the Self-Efficacy Scale for Preschool Science Education, the Science Motivation Scale for Preschool Children, and a Personal Information Form. According to the results of the analysis, there is a positive correlation between preschool teachers' self-efficacy beliefs in science education and their professional experience and educational qualifications. Furthermore, the study revealed that children's science motivation was not affected by their age and gender. Moreover, there was a positive relationship between the frequency of hands-on science activities and both teachers' self-efficacy beliefs and children's science motivation. Above all, a significant positive relationship was found between children's science motivation and teachers' self-efficacy perceptions towards science. In conclusion, this study suggests that more time should be allocated to science activities in preschool education and that programs that support the development of preschool teachers' self-efficacy in science should be included. In this way, teachers' confidence and competence in teaching science can be increased and positive effects can be created on children's interest and motivation in science from an early age.